Conflicts of interest, reputation, and the interwar debt crisis: Banksters or bad luck? - Marc Flandreau; Norbert Gaillard; Ugo Panizza (Graduate Institute of International and Development Studies, 2010)
This paper builds a new dataset with detailed information on the universe of foreign government bonds issued in New York in the 1920s and uses these data to describe the behavior of the financial intermediaries which operated in the New York market during the period leading to the interwar debt crisis. The paper starts by showing that concerns over reputation played an important role in intermediaries' underwriting choices. Next, the paper checks whether banks managed to charge abnormal underwriting fees on bonds that would eventually default and finds no evidence of such practice (banksterism). The paper concludes by discussing some parallels between the experience of the 1920s and the current debate on the originate and distribute model.
Keywords: 330; Öffentliche Anleihe; Portfolio-Management; Finanzintermediation; New York (NY); Internationale Staatsschulden; USA